IMPLEMENTASI PROGRAM BELAJAR DARI RUMAH (BDR) DALAM PEMBELAJARAN BAHASA INDONESIA PADA MASA PANDEM KORONA - Annisa Tiara Kusuma; Laili Etika Rahmawati (Universitas Pendidikan Ganesha, 2021)
The purpose of this research is to describe the planning, implementation, and evaluation of Indonesian language learning during the corona pandemic through a home learning program (BDR) in grade VIII students of Karanggede Boyolali Integrated MTs. This study uses qualitative methods. Data collection techniques used are teacher interviews and questionnaires given to students. The subjects of this study were Indonesian language teachers and grade VIII students of Karanggede Boyolali Integrated Mts. Based on the results of research on Indonesian language learning planning conducted by teachers include: Preparing KI and KD, Preparing syllabus, Preparing RPP prepared 1 sheet only and RPP made 1 meeting, Preparing prota and promes, Preparing academic kalander. Implementation of Indonesian language learning in Integrated MTs Karanggede Boyolali with method on came-close came. Evaluation of learning is done by reviewing meriview material with the holding of a short quiz, and for daily replays is done by submitting questions through google form. Recommended in activities through home learning programs (BDR), teachers are able to design learning activities from planning to evaluation in a simpler, creative and effective way.